Encyclopedia of Life Sciences 2010
DOI: 10.1002/9780470015902.a0000506.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Bursa of Fabricius

Abstract: The bursa of Fabricius plays a central role in the development of the antibody‐producing B‐lymphocyte lineage in birds. It consists of more than 10 000 follicles surrounded by connective tissue. These follicles provide an appropriate microenvironment for generating a primary repertoire of antibodies. Immunoglobulin gene diversification is achieved by gene conversion and is antigen independent. Follicular B cells undergo very rapid cell division while expressing several genes also expressed in proliferating ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…These results indicated that there were differences in cell proliferation and apoptosis. Previous research had demonstrated that only approximately 5% of daily B-cell production survives to form a mature postbursal B-cell population, which supports the observation that there were frequent B cell apoptosis and proliferation in the brusa [4]. Therefore, we inferred that cell cycle, apoptosis and proliferation were different between two duck breeds, which can influence the quantities of mature functional B cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results indicated that there were differences in cell proliferation and apoptosis. Previous research had demonstrated that only approximately 5% of daily B-cell production survives to form a mature postbursal B-cell population, which supports the observation that there were frequent B cell apoptosis and proliferation in the brusa [4]. Therefore, we inferred that cell cycle, apoptosis and proliferation were different between two duck breeds, which can influence the quantities of mature functional B cells.…”
Section: Discussionsupporting
confidence: 84%
“…The GO terms, such as cellular response to stimulus, cellular communication, receptor activity, enriched the most target genes. The bursa of Fabricius, with many B cells, is one of essential immune organs [ 4 ]. The mature B cells can synthesis immunoglobulin and it had affirmed that there are IgM, IgG, and IgA in avian, which had a role in immune response to fight infection, cytotoxicity, cytolysis and neutralize virus infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of the antibodyproducing B-lymphocyte lineage in birds mostly takes place in bursa (Mustonen et al 2010). Our data clearly demonstrate that N. sativa seed is able to induce changes in histomorphometric parameters of bursa of Fabricius where bursal follicles of birds treated with N. Sativa especially at the highest dose were larger and more frequent as compared to control group.…”
Section: Resultssupporting
confidence: 53%
“…Until sexual maturity at 4-6 months, it is the place of B cell differentiation. Subsequently, the bursa regresses completely and the B cells migrate to secondary lymphatic organs and the blood, from then on representing the peripheral B cell pool (Mustonen et al 2001).…”
Section: Introductionmentioning
confidence: 99%